With a little help from my (undesirable) friends: The influence of sex ratio on preferences for the relative mate value of friends - CHOY, Bryan Kwok Cheng (Institutional Knowledge at Singapore Management University, 2020)
The present research examined whether who men and women choose to befriend reflects evolved desires for managing intrasexual competition for mates. It is reasoned that individuals should display a stronger preference for others of relatively lower mate value to oneself when the local ecology exhibits signs of intense intrasexual competition (when the operational sex ratio [OSR] is most unfavorable). Conversely, an unfavorable OSR was expected to reduce the desirability of others of similar or higher mate value. The possibility that this effect would be sex differentiated was also examined. In particular, it was reasoned that these predictions should hold for women (men) evaluating targets who varied on their levels of physical attractiveness (social level). Two studies (NStudy 1 = 142, NStudy 2 = 69) were conducted to test these predictions. In contrast to the predictions, individuals generally preferred targets of relatively similar or higher mate value to oneself; this effect was generally consistent across both an unfavorable and favorable OSR. Nonetheless, some evidence was found that supports the proposed theoretical framework; it was shown that OSR can have some level of influence on individuals’ friendship preferences, and this influence may be sex-differentiated. Overall, the findings are evaluated as consistent with a broader view that individuals select their friends on the basis of costs and benefits. Alternative interpretations, limitations, and future directions are discussed.